Immunophenotyping of Patients With Rheumatoid Arthritis Reveals Difference in CD27+IgD+ Unswitched Memory B Cell Profiles - Bérénice Hansen; Raul Da Costa; Dominique Revets; Fanny Hedin; Maria Konstantinou; Eduardo Rosales Jubal; Franck Ngangom; Cédric C. Laczny; Kirsten Roomp; Viacheslav Petrov; Andreas Michalsen; Etienne Hanslian; et al. (Mediators of Inflammation)
Conclusion: Our results reveal, for the first time, that a reduced frequency of unswitched mB cells in patients with RA is the only significant abnormality distinguishing patients with RA from HC in a complex immunophenotyping panel of 72 different cell populations. This provides important information to further individualize various interventions and possibly help to design novel therapeutic interventions.